A survey on success factors and obstacles for further adoption of agile in IT organisations. (2017) - Bello, Mannir; Ghani, Imran
These days IT organisations aspire to implement effective and efficient processes and practices for their software development. One such attempt is by trying to implement agile software development methodologies. Indeed, agile methodologies offer some useful advantages to organisations. These benefits include high team collaboration and customer satisfactions. Numerous agile software development methods such as Scrum, extreme programming (XP), Feature driven development, Kanban, dynamic system development method (DSDM) among many are often being used by various IT organisations. Several studies have shown the success and failure of adoption of agile methods or practices. Our research presents a number of additional critical success factors and obstacles by asking from agile practitioners. Moreover, this paper presents a review of some of the existing studies also. The purpose of this survey is use to present a brief guide related to success factors and obstacles of agile adoption in some companies.